Factor influencing civic development among preservice teachers in higher education (HE) context - Ahrari, Seyedali; Othman, Jamilah; Hassan, Salleh; Abu Samah, Bahaman (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Developing students as future citizens is the oldest educational goal for educators. Constructivism as a learner-centered educational approach is used for studying the development of civic outcome. The bringing civic mission of HE is needed for a responsible specially for future teachers as agents of change. Based on a receding civic mission of HE, it can be used to foster civic outcome. In this developmental view, students are able to expand their civic skills with active participation. Tools are used in HE play a significant role in developing sense of citizenship among its students can vary from individual, personal and familial factors to curricular issues. This paper tries to confirm the relationship between important aspects HE and student personally traits to develop civic outcomes in a manner of constructive theories.